Kepemimpinan, Kedisiplinan, dan Kepuasan Kinerja Guru PNS Sekolah Dasar - Susilowati Susilowati (Philanthropy: Journal of Psychology, 2018)
The focus of this research is the influence of leadership, discipline and teacher satisfaction with the performance of civil servants in the district Jekulo rate in elementary. The purpose of this study was to determine and analyze the impact of school leadership, discipline and satisfaction with the performance of primary school teachers in the district PNS Jekulo. The method in this research is quantitative. Data collection techniques are interviews and observation. The results of the analysis leads to the conclusion of school leadership directly affects the performance of teachers, discipline has no direct influence on the performance of teachers because kedisilpinan has become the custom of a rule that must be followed by teachers, job satisfaction has no direct influence on the performance of teachers, leadership directly influence job satisfaction, kedisilpinanberengaruh directly against complacency, no school leadership indirect effect on teacher performance through customer satisfaction and discipline indirect effect on the performance of teachers through job satisfaction.